0214 The Relationship Between Work Stress and Sleep Quality in Shift Working Nurses: The Intermediate Effect of Circadian Rhythm Amplitude and Stability. (27th May 2020) - Wu, S; Wu, C; Wang, X; Fei, W; Ma, Y; Fu, Y
Abstract: Introduction: Research suggests that work stress may be an important factor in poor sleep in shift working nurses. However, evidence is limited about the underlying mechanism. Circadian rhythm might be effective. The purpose of this study was to explore the relationship between work stress and sleep quality in shift working nurses and the mediation effect of circadian rhythm amplitude and stability respectively. Methods: A total of 529 nurses working in shifts from seven hospitals were selected by convenient sampling in Shanghai, China. Participants were assessed with the Circadian Type Inventory (CTI), Chinese Nursing Stressor Scale (CNSS), Pittsburgh Sleep Quality Index (PSQI). The Amos24.0 software was applied to construct structural equation models with circadian rhythm amplitude (LV) and circadian rhythm stability (FR) as intermediate variables respectively. Results: About 73.3% (388/529) of the nurses' PSQI scores were above 5, indicating poor sleep quality. The correlations between work stress, circadian rhythm amplitude, circadian rhythm amplitude and sleep quality were all significant (all P<0.01).Sleep quality total score was positively correlated with work stress(γ=0.348) and circadian rhythm amplitude (γ=0.330). Work stress was positively correlated with circadian rhythm amplitude (γ=0.297, P<0.01). Sleep quality total score was negatively correlated circadian rhythm amplitude (γ=-0.204, P<0.01);Work stress was negatively correlated with circadian rhythm amplitude (γ= -0.284, P<0.01).Work stress showed significant indirect effects on sleep quality through the mediating effect of circadian rhythm amplitude (β=0.188, P<0.01) and circadian rhythm amplitude (β= 0.082, P<0.05). Conclusion: It suggests that nurses working in shifts have poor sleep quality. Work stress and the amplitude and stability of circadian rhythm could affect sleep quality, and circadian rhythm amplitude and stability could mediate the relationship between work stress and sleep quality. Support: The work was supported by Xinglin Young Talent Program of Shanghai University of Traditional Chinese Medicine(to Caiqin Wu) and The 12th Innovative activities of college students of Shanghai Traditional Chinese Medicine(2019SHUTCM094).